2019–2020 Florida Citrus Production Guide: Citrus Leafminer - Lauren Marie Diepenbrock; Jawwad Qureshi; Lukasz Stelinski; Philip A. Stansly (EDIS)
This 4-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written Lauren Marie Diepenbrock, Jawwad Qureshi, Lukasz Stelinski, and Philip A Stansly, and published by the Entomology and Nematology Department, March 2019.